Effect of Pre-treatment and Seed Size on Germination Components, Marketable yield and Some Characteristics of Bulb Red Azarshahr Genotype and Zargan Cultivar Onion (Allium cepa L.) - موسی ایزدخواه شیشوان; مهدی تاج بخش شیشوان (علوم و فناوری بذر ایران, 2018)
In order to evaluate the effect of priming and seed size on germination components, marketable yield, and some characteristics of bulb onion Red Azarshahr genotype and Zargan cultivar a factorial field experiment based on a randomized complete block design with three replications was conducted in 2012 and 2013 cropping season in laboratory and research field at Agriculture and Natural Resources Research Center of East Azarbayjan, Iran. The experimental treatments included priming (at four levels: hydropriming with distilled water for 4 hrs, halopriming with %2 KNO3 for 8 hrs, priming with falommin amino acid with 2% for 8 hrs and control (without priming), seed size (at three levels: small, medium, large), and the study of genotype and cultivar were Red Azarshahr and Zargan. Germination components such as shoot lengt, root lengt , seedling length , seedling vigor index, marketable yield and some onion characteristics such as percentage of class I, class II and class III, thick-neck, percentage double bulbs, fusarium infected bulbs percent, sprout number and percentage of bulbs containing multiple centers (PMC) were studied. Results showed that seed priming and seed size improved germination components and marketable yield. The highest germination percentage, seedling vigor index marketable yield were obtained from plant that primed with folammin amino acid 97.75 percent, 697.83 and 43.87 ton/ha respectively, and the lowest were achieved from control (unprimed).